EVENT MANAGEMENT IN SOCIAL ENTREPRENEURSHIP: A BIBLIOMETRIC ANALYSIS - Evanthi, Ayundha; Azhar, Ratih Mukti (Jurnal Mebis, 2023)
Social entrepreneurship is a growing phenomenon that is currently attracting much public attention due to its potential to reduce social problems and improve people's well-being. Events hosted by social entrepreneurs may present vital chances for venues to enhance the event's goal and happiness. This study aims to (1) examine event management and social entrepreneurship while focusing on the relationships, dimensions, and context-specific functions that each play, and (2) identify the link between social entrepreneurship and event management so that it can be used to construct future theories. This study uses VOSviewer to visualize how event management and social entrepreneurship were meant from numerous earlier papers using bibliometric analysis. The findings of this study will contribute to our understanding of how event management may be used in social entrepreneurship to increase behavioral intention and improve event experiences. For further research, the recommendations listed below are provided. Researchers may also develop new theories and event management literature to further the discussion and research on this subject.